Broad-spectrum pH functional chitosan–phosphatase beads for the generation of plant-available phosphorus: utilizing the insoluble P pool - Konwar, Kasturika; Boruah, Himanku; Gogoi, Rimjim; Boruah, Anudhriti; Borgohain, Arup; Baruah, Madhusmita; Gogoi, Subham Protim; Karak, Tanmoy; Saikia, Jiban (Frontiers in Chemistry, 2024)
Utilization of organic phosphates and insoluble phosphates for the gradual generation of plant available phosphorous (P) is the only sustainable solution for P fertilization. Enzymatic conversions are one of the best sustainable routes for release of P to soil. Phosphatase enzyme aids in solubilizing organic and insoluble phosphates to plant available P. We herein report the preparation of highly functional chitosan beads (CB) co-immobilized with acid phosphatase and alkaline phosphatase enzyme via glutaraldehyde linkage. The dual enzyme co-immobilized chitosan beads were characterized using FTIR, TGA and SEM to confirm the immobilization. The co-immobilized system was found to be active for a broader pH range of ~4–10 compared to the individually bound enzymes and mixed soluble enzyme. The bound matrix exhibited pH optimum at 6 and 9 respectively for acid and alkaline phosphatase and temperature optimum at 50 °C. The phosphate solubilizing ability of the chitosan-enzyme derivatives were examined using insoluble tri-calcium phosphate (TCP) for wide pH conditions of 5.5, 7 and 8.5 upto 25 days. The liberation of phosphate was highest (27.20 mg/ml) at pH 5.5 after the defined period. The soil residual phosphatase activity was also monitored after seven days of incubation with CBE for three different soil types of pH ~5.5, 7 and 8.5. The residual phosphatase activity increased for all the soils after the application of the CBE. The germination index of Oryza sativa (rice) plant was also studied at different pH buffer medium upon the application of the CBE in presence of TCP as phosphate source. Overall, the dual enzyme co-immobilized chitosan beads were highly effective over a wide pH range for the generation of plant available phosphates from insoluble phosphates. The chitosan-enzyme derivative holds the potential to be used for sustainable phosphorous fertilization with different insoluble and organic phosphorous sources